Enzymology and Regulation of δ1-Pyrroline-5-Carboxylate Synthetase 2 From Rice - Sabbioni, Giuseppe; Funck, Dietmar; Forlani, Giuseppe (Frontiers in Plant Science, 2021)
Under several stress conditions, such as excess salt and drought, many plants accumulate proline inside the cell, which is believed to help counteracting the adverse effects of low water potential. This increase mainly relies upon transcriptional induction of δ1-pyrroline-5-carboxylate synthetase (P5CS), the enzyme that catalyzes the first two steps in proline biosynthesis from glutamate. P5CS mediates both the phosphorylation of glutamate and the reduction of γ-glutamylphosphate to glutamate-5-semialdehyde, which spontaneously cyclizes to δ1-pyrroline-5-carboxylate (P5C). In most higher plants, two isoforms of P5CS have been found, one constitutively expressed to satisfy proline demand for protein synthesis, the other stress-induced. Despite the number of papers to investigate the regulation of P5CS at the transcriptional level, to date, the properties of the enzyme have been only poorly studied. As a consequence, the descriptions of post-translational regulatory mechanisms have largely been limited to feedback-inhibition by proline. Here, we report cloning and heterologous expression of P5CS2 from Oryza sativa. The protein has been fully characterized from a functional point of view, using an assay method that allows following the physiological reaction of the enzyme. Kinetic analyses show that the activity is subjected to a wide array of regulatory mechanisms, ranging from product inhibition to feedback inhibition by proline and other amino acids. These findings confirm long-hypothesized influences of both, the redox status of the cell and nitrogen availability, on proline biosynthesis.